Quercetin Pretreatment Attenuates Hepatic Ischemia Reperfusion-Induced Apoptosis and Autophagy by Inhibiting ERK/NF-κB Pathway - Liwei Wu; Qinghui Zhang; Weiqi Dai; Sainan Li; Jiao Feng; Jingjing Li; Tong Liu; Shizan Xu; Wenwen Wang; Xiya Lu; Qiang Yu; Kan Chen; et al. (Gastroenterology Research and Practice)
Background. Hepatic ischemia reperfusion (IR) injury is a common phenomenon in transplantation or trauma. The aim of the present study was to determine the protective effect of quercetin (QE) on hepatic IR injury via the ERK/NF-κB pathway. Methods. Mice were randomized into the sham, IR, QE100 + IR, and QE200 + IR groups. Quercetin was administered intragastrically daily at two doses (100 mg/kg and 200 mg/kg) for 5 days prior to IR injury. The expression levels of liver enzymes, inflammatory cytokines, and other marker proteins were determined at 2, 8, and 24 hours after IR. And they were compared among these groups. Results. Compared with the IR group, the treatment of QE reduced the release of cytokines, leading to inhibition of apoptosis and autophagy via downregulation of the ERK/NF-κB pathway in this model of hepatic IR injury. Conclusion. Apoptosis and autophagy caused by hepatic IR injury were inhibited by QE following a reduction in the release of inflammatory cytokines, and the relationship between the two may be associated with inactivation of the ERK/NF-κB pathway.